Incidence and anatomic localization of oral candidiasis in patients with AIDS hospitalized in a public hospital in Belo Horizonte, MG, Brazil - Ilanna G. Gableri; Anne C. Barbosa; Raquel R. Velela; Sandra Lyon; Carlos A. Rosa (University of São Paulo, 2008)
The objective of this study was to evaluate the incidence, anatomic localization and yeast species isolated from each clinical type of oral candidiasis. The clinical samples were obtained from 67 patients with AIDS with CD4 cell counts below 200 cells/mm³ and hospitalized in a public hospital (Eduardo de Menezes Hospital) in the city of Belo Horizonte, MG, Brazil. Yeasts were isolated using Chromagar® Candida. The results show that 50.7% of these patients had oral candidiasis. The pseudomembranous form was the most frequent clinical manifestation of oral candidiasis, followed by the erythematous and angular cheilite forms. The most common site of these clinical forms of oral candidiasis was the tongue. Candida albicans was the most common yeast species isolated from the lesions. However, other species were also found to be associated with these forms of oral candidiasis.